Building Information Modeling (BIM) and Construction Simulation - Welty, Christopher (ARCC Conference Repository, 2019)
Experimentation remains at the heart of teaching architectural design with studio being the main vehicle for architectural education. It provides the foundation for architectural creativity and knowledge, as well as establishing the framework for thinking, understanding and creating architecture. Organized around the development of a real project, studio class has a unique opportunity to investigate many themes. The question of digital technology integration within the studio remains an open debate within the Professional Program at Southern Polytechnic State University (SPSU). Given the ubiquity of digital technology within the profession, integration seems like a natural progression within architectural education. The third-year serves as an academic bridge within our program at SPSU. Spring semester seeks to explore the paradigm of design ideas through systems research and construction simulation while focusing on a vertically organized building in a dense urban context. The studio assignment integrates the content of technical support courses within our curriculum. It emphasizes the exploration of environmental and sustainable design strategies and encourages the students to examine enclosure systems as generators of building form and aesthetic solutions. The digital environment can provide an excellent tool for thinking about architectural conditions, both as object and subject. My third-year studio section explored the integration of building technology throughout the design process with "Building Information Modeling” (BIM). This studio was not directed towards digital computation as a generator of form nor as a pure representational and documentation tool, but instead, we experimented with virtual modeling during the design process to understand and test their design solutions.